2015
DOI: 10.3390/ijms16059134
|View full text |Cite
|
Sign up to set email alerts
|

PRRT2 Mutant Leads to Dysfunction of Glutamate Signaling

Abstract: Paroxysmal kinesigenic choreoathetosis (PKC) is an inherited disease of the nervous system. We previously identified PRRT2 as the causative gene of PKC. However, as little is known about the function of PRRT2, elucidating its function will benefit not only PKC studies, but also many other related disorders. Here, we reveal higher levels of glutamate in the plasma of PKC patients and the culture medium of neurons following knock-out Prrt2 expression. Using double immunostaining assays we confirm Prrt2 is locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 59 publications
9
51
0
Order By: Relevance
“…We also examined the distribution of EGFP-Prrt2 in transfected cultured HEK293T cells (Figure 2B, right panel). The fluorescence signals from EGFP and Prrt2 antibody predominantly co-localized at the cell membrane, consistent with previous observations using other protein tags [1, 20]. To further test the specificity of the antibody, we test whether knocking down Prrt2 expression in cells by RNA interference (RNAi) will eliminate antibody reactivity (Figure 2C).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…We also examined the distribution of EGFP-Prrt2 in transfected cultured HEK293T cells (Figure 2B, right panel). The fluorescence signals from EGFP and Prrt2 antibody predominantly co-localized at the cell membrane, consistent with previous observations using other protein tags [1, 20]. To further test the specificity of the antibody, we test whether knocking down Prrt2 expression in cells by RNA interference (RNAi) will eliminate antibody reactivity (Figure 2C).…”
Section: Resultssupporting
confidence: 85%
“…Recent studies have revealed that PRRT2 is a component of the AMPAR (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor) complex [30, 31] and may be involved in neurotransmitter release and glutamate signaling[20, 32]. Consistently, PRRT2 was found to co-localize with pre- and post-synaptic markers vGlut1 and PSD95 in our study.…”
Section: Discussionsupporting
confidence: 88%
“…There is evidence that PRRT2 localizes mostly in axons of glutamatergic synapses [41,42]. However, previous works have suggested that it interacts with the SNARE protein SNAP-25 as well as the GluA1 subunit of the AMPA-type glutamate receptor complex, leaving the question open of whether PRRT2 localizes at the presynaptic terminal, postsynaptic terminal, or both.…”
Section: A Pathophysiological Frameworkmentioning
confidence: 99%
“…Finally, proteomic studies demonstrated an interaction of PRRT2 with the AMPA receptor complex [49]. After infection with shRNA-Prrt2 lentivirus, there is an increase in glutamate levels in the culture medium of neurons as well as in the distribution of GluA1 on the cell membrane [42]. One of the reasons why carbamazepine is very effective in patients with PRRT2 mutations might be owing to its ability to enhance the activity of the glutamate transporter 3 at the post-synaptic terminal [50], thus allowing glutamate to be pumped into postsynaptic terminals without activating its receptor.…”
Section: A Pathophysiological Frameworkmentioning
confidence: 99%
“…A minority of patients with heterozygous SLC2A1 mutations develop isolated PED [11, 1517]. PRRT2 encodes proline-rich transmembrane protein 2, which interacts with SNAP25 and thereby influences the release of glutamate or other neurotransmitters [18]. Heterozygous PRRT2 mutations have been found in patients with several paroxysmal neurologic disorders including PKD [19].…”
Section: Introductionmentioning
confidence: 99%